Technical-tactical performance profile of the block and dig according to competition category in men's volleyball - Antonio García-; Enrique Ortega; José M. Palao (Universidade Estadual Paulista (UNESP), 2016)
Abstract The aim of this study was to analyse the technical-tactical performance profile of blocking and court defence actions for various age groups and categories of competition in men's volleyball. The sample comprised 16,454 blocks and 8,321 digs performed in 299 sets in several categories of competition (from U-14 to Olympic Games). A descriptive and correlational inter- and intra-group observational design was used. The variables studied were: category of competition, opponent's spike tempo, and block and dig performance. The results showed a significant increase in the percentage of blocks and digs derived from fast attacks and a significant improvement in performance of these actions to counteract slow attacks. Thus, improving in blocking and digging performance was observed at higher categories when the attack is performed slowly. This paper discusses various reasons for the evolution in defensive performance and the effects on the training process for various categories of competition in volleyball.